2023
DOI: 10.3390/ijms24065842
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpenoid Epoxidiol Ameliorates the Pathological Phenotypes of the Rotenone-Induced Parkinson’s Disease Model by Alleviating Mitochondrial Dysfunction

Abstract: Parkinson’s disease is the second most common neurodegenerative disease. Unfortunately, there is still no definitive disease-modifying therapy. In our work, the antiparkinsonian potential of trans-epoxide (1S,2S,3R,4S,6R)-1-methyl-4-(prop-1-en-2-yl)-7-oxabicyclo [4.1.0]heptan-2,3-diol (E-diol) was analyzed in a rotenone-induced neurotoxicity model using in vitro, in vivo and ex vivo approaches. It was conducted as part of the study of the mitoprotective properties of the compound. E-diol has been shown to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 101 publications
1
5
0
Order By: Relevance
“…Stressful environment results in free radicals' production which interacts with oxygen molecules on membrane lipids to produce peroxy radicals, which are accountable for lipid peroxidation represented by MDA (Rizk et al, 2018;Aziz et al, 2022). Our research reveals that rotenone-treated mice showed elevated MDA levels, as reported by others (Mohammad et al, 2023;Aleksandrova et al, 2023) whereas such enhancement is restored to normal using L-dopa and the iridoids-rich fraction isolated from Pentas lanceolata (PIRF) leaves as results in decrease in MDA level.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Stressful environment results in free radicals' production which interacts with oxygen molecules on membrane lipids to produce peroxy radicals, which are accountable for lipid peroxidation represented by MDA (Rizk et al, 2018;Aziz et al, 2022). Our research reveals that rotenone-treated mice showed elevated MDA levels, as reported by others (Mohammad et al, 2023;Aleksandrova et al, 2023) whereas such enhancement is restored to normal using L-dopa and the iridoids-rich fraction isolated from Pentas lanceolata (PIRF) leaves as results in decrease in MDA level.…”
Section: Discussionsupporting
confidence: 71%
“…The enzyme acetylcholine esterase (AChE) is the key enzyme in the hydrolysis of the neurotransmitter acetylcholine and is also the target of most of the clinically used agents for the treatment of PD (Wang et al, 2020). AChE level in brain homogenates of different treated groups was represented in Figure (9). Rotenone treatment had decreased the AchE level by 40.5%.…”
Section: D) Biochemical Resultsmentioning
confidence: 99%
“…The activity of electron transport chain complexes was assessed in preparation of the mitochondrial p2 fraction of the brain (10 µg/well) using the Agilent Seahorse XF96e Analyzer (Seahorse Bioscience, USA) to measure the rate of oxygen uptake triggered by modulators as described early [32]. For this purpose, the activators of the electron transport chain complex Iglutamate/malate, the inhibitor of the complex I -rotenone (2 µM), the substrate of the difficult IIpotassium succinate (2 µM), the inhibitor of the complex III -antimycin A, and the substrates of the complex IV -0.5 µM ascorbate/tetramethyl-p-phenylenediamine (TMPD) were used.…”
Section: Bioenergetic Characteristics Of the Mitochondriamentioning
confidence: 99%
“… 13 , 14 In neurons, rotenone inhibits respiratory chain complex I in the mitochondria and subsequently induces the production of reactive oxygen species (ROS) and mitochondrial dysfunction, leading to progressive damage of dopaminergic neurons. 14 , 15 Pathological changes induced by rotenone are not limited to dopaminergic neuron deterioration, 16 18 but also include overactivation of microglia adjacent to the neurons. Sherer et al revealed that rotenone can activate microglia in rodent PD models before the anatomical pathology results in dopaminergic neurons loss.…”
Section: Introductionmentioning
confidence: 99%